IMPROVING STUDENTS’ VOCABULARY MASTERY IN READING COMPREHENSION THROUGH GAMES AT SMPN 259 JAKARTA - Lestari, Nendri Niki (IJIET (International Journal of Indonesian Education and Teaching), 2024)
This research aims to improve mastery of English vocabulary in reading comprehension through the use of game methods at SMPN 259 Jakarta. The type of research used is classroom action research using the Kemmis and McTaggart model. The subjects in this research were 33 students in class VIII at SMPN 259. The research took place over three cycles and each cycle consisted of one meeting. Data collection techniques use observation techniques and need analysis tests. Data analysis techniques use quantitative descriptive and qualitative descriptive. The results of the research show that the use of the games method can improve vocabulary mastery and students' learning outcomes in reading comprehension. In the pretest vocabulary activity, the class average score was 71.75, while the reading value was 68.18. After being given treatment for 3 cycles, the average post-test vocabulary score was 91.13 and the post-test reading score was 86.95. With this, it can be concluded that through the game method, students' reading comprehension ability increased by 27%.